Green space optimization for rural vitality: Insights for planning and policy. (September 2021) - Lin, Yongyuan; Shui, Wei; Li, Zhipan; Huang, Shan; Wu, Kexin; Sun, Xiaorui; Liang, Jingchen
Abstract: In the process of rapid urbanization, rural areas have undergone substantial transformations. Although changes from the internal villages, rural actors as masters of the village respond to the implementation of top-down policy and planning passively. It results in the village short of vitality and cohesion and the mismatch between policy and actual situations. It is necessary to incorporate ecosystem services knowledge into the village planning and policy-making in order to provide more supports for the implementation of local government policies. This article proposes a process for interactive participation to optimize green space in the peri-urban village from the demand-side perspective. In this contribution, rural stakeholders' interactive participation can make green infrastructure optimization more impartial. In addition, cultural squares play an important role in strolling outwards, fitness, and being close to nature, as well as promoting recreation. Both higher access frequency and closer distance from home to the green infrastructure generate climatic benefits, community and social benefits, and place attachment. We propose that village planning should include infrastructure sector planning in the high-density villages with bottom-up interactive participation and a top-down rural homestead system. It is an important way to make land use policy and realize rural revitalization and transformation in similar human settlements in the world. Graphical Abstract: ga1 Highlights: A process for interactive participation including public stakeholders to prioritize land use in peri-urban areas was proposed. Hydrophilic areas including coastal parks have the more social value for ecosystem services. Impartial configuration of green infrastructure is an important way for rural vitality. Case study of participatory mapping methods is an exploratory technology demonstration.